Editorial - Robles Olivos, Rafael (2022)
Digitally hyperconnected, and increasingly techno-dependent, humanity travels on a high-speed train called the Internet. Still not sure where heading, how to stop, change course, or pause in one of the infinite stations that make up cyberspace. However, despite to this initial bewilderment and to setbacks such as that of Cambridge Analytica in 2018, the average netizen doesn’t seem to have any intention of backing down or stop midway, despite how uncertain it is. At least to short and medium term there are no plans to buy the return ticket.